Carbon sequestration potential, challenges, and strategies towards climate action in smallholder agricultural systems of South Asia - Jat, Mangi Lal; Chakraborty, Debashis; Ladha, Jagdish K.; Parihar, Chiter Mal; Datta, Ashim; Mandal, Biswapati; Nayak, Harisankar; Maity, Pragati; Rana, Dharamvir Singh; Chaudhari, Suresh K.; Gerard, Bruno G. (Elsevier, 2022)
South Asia is a global hotspot for climate change with enormous pressure on land and water resources for feeding the burgeoning population. The agricultural production systems are highly vulnerable in the region and is primarily dominated by small and marginal farmers with intensive farming practices that had favored the loss of carbon (C) from soil. This review discusses the potential of soil and crop management practices such as minimum/reduced/no-tillage, use of organic manure, balanced and integrated plant nutrient application, precision land levelling, precision water and pest management, residue management, and cropping system optimization to maintain the C-equilibrium between soil and atmosphere and to enhance the C-sequestration in the long run. Results of meta-analysis show a potential 36% increase in soil organic C stock in the top 0–15 cm layer in this region which amounts to ∼18 Mg C stocks ha−1. Improved management practices across crops and environment may reduce methane em0ission by 12% resulting in an 8% reduction in global warming potential (GWP), while non-submerged condition led to a 51% GWP reduction in rice. Conservation agriculture and precision fertilization also reduced GWP by 11 and 14%, respectively. Although several innovative climate resilient technologies having significant potential for C-sequestration have been developed, there is an urgent need for their scaling and accelerated adoption to increase soil C-sequestration. Policies and programs need to be devised for incentivizing farmers to adopt more C-neutral or C-positive agricultural practices. The national governments and other agencies should work towards C farming together with global initiatives such as the “4 per 1000” Initiative and Global Soil Partnership, and regional public-private partnership initiatives on carbon credits for Regenerative Agriculture such as by Grow Indigo-CIMMYT-ICAR in India, in addition to research and policy changes. This will be vital for the success of soil C sequestration towards climate action in South Asia.